2014
DOI: 10.1097/bsd.0b013e318277da19
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Comparison of Atlantoaxial Fusion With Transarticular Screws and Screw-Rod Constructs

Abstract: TAS and SRC are safe and effective treatment options for C1-C2 instability but require a thorough knowledge of atlantoaxial anatomy for successful insertion of screws. Slightly higher rates of fusion and less risk of injury to the vertebral artery during screw placement were observed with the SRC technique. However, differences in graft material and techniques were noted. Prospective, randomized studies with validated radiographic and clinical outcome metrics are necessary for proper comparison of these techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 66 publications
(83 reference statements)
3
50
1
8
Order By: Relevance
“…9) for C1-C2 fixation. This instrument provides excellent immobilization with fewer complications compared with other posterior atlantoaxial fixation instruments [2,[30][31][32][33][34]. Since then, this technique has become increasingly popular [35].…”
Section: Screw-rod Systemmentioning
confidence: 98%
“…9) for C1-C2 fixation. This instrument provides excellent immobilization with fewer complications compared with other posterior atlantoaxial fixation instruments [2,[30][31][32][33][34]. Since then, this technique has become increasingly popular [35].…”
Section: Screw-rod Systemmentioning
confidence: 98%
“…[345] Comparative biomechanical and long-term studies of the surgical fixation techniques performed in this region are present in the literature. [23456789101112] Lately, translaminar fixation technique is becoming more popular. [13] The selection of the fixation technique for C1-C2 posterior arthrodesis surgery depends on a lot of factors such as the anatomy of the upper cervical vertebrae (C1 and C2), anomalies, deformities, VA variations, nonreductable fractures and most importantly the experience of the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Despite that, it is stated in the latest publications that the complication rates with Goel technique might just be as high as in Magerl technique. [11] Finn et al performed Magerl technique on 269 cases, indicated 15% complication rate of which one case was fatal, and reported that this technique has many disadvantages. [16]…”
Section: Discussionmentioning
confidence: 99%
“…24 Also, comparison with Magerl's technique has shown similar biomechanical characteristics for both stabilization methods. 25 Posterior element integrity is not a necessity for this technique as it can be applied in fractures of the laminae. 26 In addition, the provided biomechanical construction sustained by polyaxial screws and rods allows for corrective intraoperative surgical manipulations to the occipitocervical junction.…”
Section: Discussionmentioning
confidence: 99%